(untitled) (Research, Society and Development, 2021)
Introduction: The COVID-19 pandemic has drastically changed the work routine of healthcare professions leading to activities overload, physical exhaustion, and significant changes in mental health. Objective: To investigate the occupational stress among nursing professionals during the COVID-19 pandemic in Brazil. Methods: This is a cross-sectional study conducted through an anonymous online questionnaire. Data collection was performed by using social media including Facebook, WhatsApp, Instagram, and e-mail. We analyzed associations between the outcome of interest and independent variables calculating the prevalence ratio (PR) with 95% confidence interval (CI). The Cochran-Armitage test was used to assess the PR according to the different categories for the following variables: education, income, and level of care. The significance level was set at 5%. Results: Of the 2986 nursing professionals included in the present study, 2704 (90,6%; 95% CI 89,5 – 91,6) reported occupational stress during the COVID-19 pandemic. An increase in the prevalence of occupational stress was observed with the increase in education level (p < 0.001), income (p < 0.001), and level of care (p < 0.001). Professionals with more than 20 years of professional experience also reported higher levels of occupational stress. Conclusion: Our findings show a prevalence of occupational stress of approximately 90%, being higher among nurses with a higher level of education, income, level of care.